Techno-fixers : origins and implications of technological faith - Johnston, Sean, 1956- (McGill-Queen's University Press, 2020)
"A critical examination of modern faith in technology, Techno-Fixers evaluates past mistakes, present implications, and future opportunities for innovating societies."--